Has Fiscal Decentralization Succeeded in Increasing Quality Economic Growth in East Java? (Jurnal Bina Praja, 2019)
Research on Local Revenue, General Allocation Fund, and Special Allocation Fund on economic growth, poverty, unemployment, and Gini ratios have often been done. However, there is no research that uses these three funding sources as latent variables that have a simultaneous influence on quality economic growth variables as a latent variable consisting of economic growth, poverty, unemployment and the Gini ratio as constructs. Similarly, capital expenditure as a moderating variable will be seen as influencing the source of funds. East Java is a province with 38 districts/cities where the level of economic growth is quite high and even exceeds the level of national economic growth. But the level of poverty, unemployment, and inequality is also very high. This study aims to look at the effect of decentralized funding sources on Quality Economic Growth in East Java. The data used comes from the Directorate General of Financial Balance of the Ministry of Finance in 2012 - 2015 for realization’s fund, and from the Central Bureau of Statistics for economic growth, poverty, unemployment, and Gini ratios. This study uses Partial Least Squares (PLS) in analyzing data, where quality economic growth becomes endogenous latent variables that are influenced by funding sources as exogenous latent variables and capital expenditure as a moderating variable. The results of the analysis show that the source of funds does not significantly affect quality economic growth even though the direction is positive. Likewise, capital expenditure cannot strengthen the influence of funding sources on quality economic growth. From this research, it is expected that the regional government can reanalyze the allocation of funds and the realization of regional expenditures which are prioritized for public service spending so that the triple track strategy can be implemented properly and achieve quality economic growth.
Keywords: Fiscal Decentralization; Quality Economic Growth; Funding Sources; Capital Expenditures; East Java